The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1097/ta.0000000000003056
|View full text |Cite
|
Sign up to set email alerts
|

Helping individuals with firearm injuries: A cluster randomized trial

Abstract: BACKGROUND:Patients with firearm injuries are at high risk of subsequent arrest and injury following hospital discharge. We sought to evaluate the effect of a 6-month joint hospital-and community-based low-intensity intervention on risk of arrest and injury among patients with firearm injuries. METHODS:We conducted a cluster randomized controlled trial, enrolling patients with firearm injuries who received treatment at Harborview Medical Center, the level 1 trauma center in Seattle, Washington, were 18 years o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
(32 reference statements)
0
12
0
Order By: Relevance
“…This was a qualitative study utilizing a semistructured interview format. Participants were adults ages 18 or older who were treated for an assault-related or unintentional firearm injury at Harborview Medical Center in Seattle, WA and enrolled in the Helping Individuals with Firearm Injuries (HIFI) study (Lyons et al, 2021). HIFI was a randomized controlled trial of a 6-month intervention program among victims of firearm assault and unintentional injury to address their goals and link them to community services (i.e., housing, health, substance abuse treatment, employment) with the primary aims of reducing incarceration and violence recidivism.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was a qualitative study utilizing a semistructured interview format. Participants were adults ages 18 or older who were treated for an assault-related or unintentional firearm injury at Harborview Medical Center in Seattle, WA and enrolled in the Helping Individuals with Firearm Injuries (HIFI) study (Lyons et al, 2021). HIFI was a randomized controlled trial of a 6-month intervention program among victims of firearm assault and unintentional injury to address their goals and link them to community services (i.e., housing, health, substance abuse treatment, employment) with the primary aims of reducing incarceration and violence recidivism.…”
Section: Methodsmentioning
confidence: 99%
“…Although there are some overlapping risk factors for assault and unintentional firearm injuries, there are likely some differences between these groups. Some of the participants were enrolled in the intervention arm of the original trial, which found no differences in outcomes of interest including incarceration and repeat violence after injury (Lyons et al, 2021). Given these findings, the small number of participants, and qualitative nature of the study, it is difficult to identify discernable and meaningful differences between these groups.…”
Section: Limitationsmentioning
confidence: 99%
“…But we caution against generalizing the findings to other, less-intensive HVIP models and to most individuals who suffer serious injuries due to violence. Lyons et al (2021) conducted an RCT of an HVIP that involved engagement with an intervention specialist at bedside, motivational interviewing (Stanhope et al 2016) by a support specialist to encourage risk-reducing behaviors, and a case management approach-critical time intervention (Center for the Advancement of Critical Time Intervention 2016)-adapted specifically for individuals surviving gunshot wounds. The support specialist was a master's-trained social worker person of color who was provided guidance for assisting gunshot survivors from a multidisciplinary group of individuals consisting of local community organizations, a community mental health agency, law enforcement, and other public service agencies.…”
Section: Findings From Randomized Controlled Trials (Rcts)mentioning
confidence: 99%
“…The study was conducted among patients presenting to Harborview Medical Center, a Level 1 trauma center in Seattle, Washington. The study is described in detail in Lyons et al ( 2020 ), Lyons et al ( 2021 ). The intervention goal was to support overall health and well-being, while the primary outcome was preventing arrest over two-years following hospital discharge, with a secondary outcome of preventing injury recidivism.…”
Section: Introductionmentioning
confidence: 99%
“…The Helping Individuals with Firearm Injuries (HiFi) study was launched to better understand the effectiveness of hospital-and community-based programs in reducing violence and subsequent injuries during and after recovery from gunshot wounds (GSWs) (Rowhani-Rahbar et al 2016;Lyons et al, 2021). The intervention was based on the Critical Time Intervention and included a phased intensity, with hospital and community-based interactions with the Support Specialist (Herman and Conover 2011;Tomita and Herman 2012).…”
Section: Introductionmentioning
confidence: 99%